HUBUNGAN KETAHANAN KELUARGA TERHADAP PERILAKU BERISIKO TERTULAR COVID-19 PADA REMAJA DI SMAN 1 CILEUNYI BANDUNG - Refa Refiana, Rusmawan (2021)
Adolescence is a period of transition where there are many changes, including the attitudes and behavior of adolescents that can have an impact on the surrounding environment. The family resilience system can influence attitudes and behavior in adolescents. This study aims to determine the relationship between family resilience and risk behavior for exposure to COVID-19 in adolescents at SMAN 1 Cileunyi Bandung. The method used is descriptive analytic with a cross-sectional design. The sampling technique used the probability samples technique with a total sample of 248 adolescents. The data analysis used was univariate analysis and bivariate analysis with Chi Square test and used family resilience questionnaires and risk behavior questionnaires exposed to COVID-19. The results of this study show that there is a relationship between family resilience to risky behavior exposed to COVID-19 in adolescents with (p value = 0.000). This research is useful for families to improve their family resilience system in terms of communication, approach and problem solving in order to minimize all forms of risky behavior in adolescents that can be detrimental. Keywords: Adolescents, COVID-19, Family Resilience, Risky Behavior